In vitro catabolism of rutin by human fecal bacteria and the antioxidant capacity of its catabolites - Jaganath, I.; Mullen, W.; Lean, M.; Edwards, Christine; Crozier, A. (Elsevier, 2009)
The role of colonic microflora in the breakdown of quercetin-3-O-rutinoside (rutin) was investigated. An in vitro fermentation model was used and (i) 28 µmol of rutin and (ii) 55 µmol of quercetin plus 18 × 106 dpm of [4-14C]quercetin (60 nmol) were incubated with fresh fecal samples from three human volunteers, in the presence and absence of glucose. The accumulation of quercetin during in vitro fermentation demonstrated that deglycosylation is the initial step in the breakdown of rutin. The subsequent degradation of quercetin was dependent upon the interindividual composition of the bacterial microflora and was directed predominantly toward the production of either hydroxyphenylacetic acid derivatives or hydroxybenzoic acids. Possible catabolic pathways for these conversions are proposed. The presence of glucose as a carbon source stimulated the growth and production of bacterial microflora responsible for both the deglycosylation of rutin and the catabolism of quercetin. 3,4-Dihydroxyphenylacetic acid accumulated in large amounts in the fecal samples and was found to possess significant reducing power and free radical scavenging activity. This catabolite may play a key role in the overall antioxidant capacity of the colonic lumen after the ingestion of quercetin-rich foods. © 2009 Elsevier Inc. All rights reserved.